EFFECT OF VARIOUS MULCHES ON GROWTH, YIELD AND QUALITY OF KINNOW - BHANUKAR MANOJ; SINDHU; S. S.; PREETI; PRINCE (The Bioscan, 2015)
The experiment was conducted at Research Farm of the Department of Horticulture, CCS Haryana Agricultural University, Hisar during the year 2013 to assess the effect of different mulches on growth, yield and quality of Kinnow. The treatments comprising six levels viz., control, black polythene 100 micron, black polythene 200 micron, paddy straw (5 cm thickness), sugarcane trash (5 cm thickness) and pearl millet straw (5 cm thickness) of mulches which were laid out in a randomized block design with three replications. In mulching experiment, maximum values for plant girth (6.27), spread (EW-9.28, NS- 8.55), height (8.52), fruit weight (177.41), length (7.16), breadth (7.28), number of fruits (246.72) and yield (43.77) were recorded with black polythene of 200μ mulch. However, maximum TSS (8.33), ascorbic acid (41.66) and minimum acidity (0.77) were recorded in paddy straw mulch and maximum juice content (54.58) was recorded with black polythene 200μ mulch. Leaf water potential was influenced by various mulches, but minimum leaf water potential was observed in black polythene 200μ mulch (11.50).